Effect of Cryopreserved Human Cord Blood on Leukocyte Indices in Rats - Lomako, Viktoria; Pirozhenko, Liudmyla (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(1): 058–062